Use of photographs in three malaysian english dailies - Motlagh, Nafise Esmael (2008)
This research was conducted to examine the use of photograph in Malaysian English dailies. Three newspapers with the largest circulations were chosen from English dailies: The Star, The Sun and The New Straits Times and content analysis was adopted as research method. The total number of sample was 138 issues which were selected every other day in a period between August 1 and October 30 of 2005. For pre-testing, 46 issues of The Star daily were examined in a three-month period (May, June, and July 2005) in order to improve and refine the codes. The results showed that the findings of the pre-test answer the research questions. The data were analyzed using the Statistical Package for Social Science (SPSS). Frequencies and percentages were used to summarize the data.Framing theory supported the results of this study. Framing theory reveals how the media portray the issues they cover. According to this theory, it was found that Malaysian editors in English dailies highlight the negative photographs which are mostly published in big size. This study found that, in Malaysian English dailies, nearly half of the front page photographs are not accordant to the headlines, meaning that front page photographs and the headlines do not cover the same pieces of news; the numbers are so remarkable in political headlines. It was found that Malaysian English dailies use international sources to cover Asia-Pacific news while this region has the highest number of front page photographs among Asian Regions.